EL DEBATE PERMANENTE Modos de producción y revolución en América Latina - Marchena, Juan; Chust, Manuel; Schlez, Mariano (Ariadna Ediciones, 2020)
The book that the reader has in his hands is about one of the most important scientific questions for the knowledge of the history of mankind: how do societies arise, organize, move and transform? He asks that, like the central problems of science, he does not find his origin in the narrow walls of academic fields, but rather he responds to the need that, as a society, we have to know, elucidate who we are and where we are going. De te fabula narratur: about you, about you, about me, about him, about her, about all of us, history speaks.